Skin‐Inspired Ti 3 C 2 T x MXene‐AgNWs/Silk Fibroin Composite Film for Skin Bioelectronics and Wound Management - Shuyu Wang; Zhe Fu; Jingwen Zhang; Yutong Wu; Jingyu Jiang; Rui Liu; Wen Guo; Bingjie Mai; Xinwang Yang; Ziwei Deng (Advanced Healthcare Materials, 2026)
ABSTRACT Skin bioelectronics have demonstrated significant potential in healthcare monitoring and wound management. Nevertheless, developing an innovative bioelectronics‐integrated wound dressing still poses a significant clinical challenge in wound management. Herein, we present a smart and flexible bioelectronics‐integrated wound dressing, constructed from a skin‐inspired Ti 3 C 2 T x MXene‐AgNWs/silk fibroin (MX‐Ag/SF) composite film. The MX‐Ag/SF composite film exhibits high breathability, conductivity, flexibility and stretchability, biocompatibility, and photothermal antibacterial properties. This makes it suitable for assembly into a versatile epidermal sensor for real‐time monitoring of various human physiological signals. Furthermore, both in vitro and in vivo studies demonstrate that the MX‐Ag/SF composite film significantly enhances its therapeutic efficacy in treating diabetic wounds, which is accomplished by suppressing inflammatory cell infiltration, promoting angiogenesis, enhancing re‐epithelialization, stimulating collagen deposition, inhibiting bacterial growth, and effectively controlling wound infection. In addition, the MX‐Ag/SF composite film functions as a novel flexible bioelectronic device for wound movement tracking or wound monitoring during wound healing process. This capability renders it highly promising for applications in skin bioelectronics for intelligent post‐wound monitoring and rehabilitation motion management. This study introduces a promising approach to developing an innovative bioelectronics‐integrated wound dressing, which can be applicable in skin bioelectronics for health monitoring and chronic wound management.